1998
DOI: 10.1097/00003246-199805000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Removal of endotoxin and cytokines by plasma exchange in patients with acute hepatic failure

Abstract: TNF-alpha and IL-6 may be important in the pathogenesis of the clinical symptoms that differentiate fulminant hepatitis from the severe form of acute hepatitis, and plasma exchange removes these inflammatory mediators from the circulation of patients with severe liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 23 publications
1
78
1
5
Order By: Relevance
“…This concept is supported by Knaus et al [21], who state that changes in the APACHE III score on each subsequent day of ICU therapy provide daily updates in the risk estimates. Both clinical and experimental studies have shown that plasmapheresis lowers circulating levels of endotoxin and cytokines such as tumor necrosis factor α and interleukin 1β [10,18,28,29,30]. Most authors claim that the beneficial effect of plasmapheresis is due to the removal of these mediators.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by Knaus et al [21], who state that changes in the APACHE III score on each subsequent day of ICU therapy provide daily updates in the risk estimates. Both clinical and experimental studies have shown that plasmapheresis lowers circulating levels of endotoxin and cytokines such as tumor necrosis factor α and interleukin 1β [10,18,28,29,30]. Most authors claim that the beneficial effect of plasmapheresis is due to the removal of these mediators.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Multiorgan dysfunction in ALF is believed to derive from oxidative stress due to reactive oxygen species and reactive nitrogen species 4 and from immunological injury mediated by cytokines. [5][6][7][8] N-acetylcysteine (NAC) is a thiol-containing agent that scavenges free oxygen radicals and replenishes cellular mitochondrial and cytosolic glutathione stores. [9][10][11] NAC has also been shown to directly scavenge reactive oxygen species and reactive nitrogen species.…”
Section: See Editorial On Pagementioning
confidence: 99%
“…10 A variety of toxins accumulating in the body as a result of liver injury and cytokines released directly from the necrotic liver into the circulation are considered to be responsible for the deterioration of the condition. 11 It is also reported that activated leukocytes and their proteases can contribute to the pathogenesis of liver injury. 12,13 Furthermore, severe liver injury develops both impaired productive and consumptive coagulatory disturbance resulting in DIC and fatal outcomes.…”
mentioning
confidence: 99%